Evaluation of the Hypoglycemic Effects of Flavonoids and Extracts from Jatropha gossypifolia L (2015)
ABSTARCT: Jatropha gossypifolia L. (Euphorbiaceae) is a plant widely used in the treatment of type 2 diabetes mellitus (T2DM), but there are few scientific reports validating its activity in this area. In this work and through a bioguided assay, a crude extract stimulated glucose uptake in C2C12 myotubes up to 30%, thereby reducing insulin resistance induced by fatty acids compared to the basal control. A chromatographic fraction applied intraperitoneally (IP) in mice reduced glucose by 42% in a mouse model of T2DM, after administration of 10 doses during 20 days. A flavanone was purified from this active fraction and its structure was assigned by 1H- and 13C-NMR (1D and 2D) and MS. This compound retains the previously reported activity, stimulating in vitro the glucose uptake in a concentration-dependent manner. This study indicates that Jatropha gossypifolia L. extracts enhance glucose uptake in cultured myotubes and adipocytes and also improving glucose tolerance in an in vivo model. Keywords: Jatropha gossypifolia L, Flavanone, Flavone, Glucose regulation, Myotubes, Mice